(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article examines the problems of translating phraseological units in the field of translation studies, in particular, the difficulties that arise when translating from Arabic into other languages, including Uzbek and Russian, are analyzed. The article studies the phraseological system of the Arabic language and its subtleties in translating into other languages. Phraseological units express not only the meaning contained in words, but are also associated with a certain culture, history and traditions. Correct translation of phraseologisms in the Arabic language requires a translator’s deep knowledge of the language and culture. The article presents ideas on methods for solving phraseological problems, their importance in translation, and the need to take into account the cultural context in the translation process.